Contraction of the ROS Scavenging Enzyme Glutathione S-Transferase Gene Family in Cetaceans - Ran Tian (G3: Genes, Genomes, Genetics, 2019)
Cetaceans are a group of marine mammals whose ancestors were adaptated for life on land. Life in an aquatic environment poses many challenges for air-breathing mammals. Diving marine mammals have adapted to rapid reoxygenation and reactive oxygen species (ROS)-mediated reperfusion injury. Here, we considered the evolution of the glutathione transferase (GST) gene family which has important roles in the detoxification of endogenously-derived ROS and environmental pollutants. We characterized the cytosolic GST gene family in 21 mammalian species; cetaceans, sirenians, pinnipeds, and their terrestrial relatives. All seven GST classes were identified, showing that GSTs are ubiquitous in mammals. Some GST genes are the product of lineage-specific duplications and losses, in line with a birth-and-death evolutionary model. We detected sites with signatures of positive selection that possibly influence GST structure and function, suggesting that adaptive evolution of GST genes is important for defending mammals from various types of noxious environmental compounds. We also found evidence for loss of alpha and mu GST subclass genes in cetacean lineages. Notably, cetaceans have retained a homolog of at least one of the genes GSTA1, GSTA4, and GSTM1; GSTs that are present in both the cytosol and mitochondria. The observed variation in number and selection pressure on GST genes suggest that the gene family structure is dynamic within cetaceans.